Disciplinary Comparison of Communication and Collaboration of University Faculty through ICTs - Morales Rodríguez, Ana Teresa (2016)
The disposition teachers have for resorting to communication and collaboration strategies mediated by Information and Communication Technologies (ICT) is key for establishing academic networks inside and outside the institution either at a national or international levels. With the aim of exploring the complex relationship that may exist between the usages of ICT mediated academic networks and the academic discipline, we have conducted a research on the digital tools Higher Education Educators use to communicate and collaborate with academic purposes. In this article we present the frequency educators use digitals tools and strategies for communicating, socializing and collaborating in Internet depending on the characterization of the academic discipline depending on the hardness of the discipline (soft and hard disciplines) ant its purity (pure and applied disciplines).